Development of Historical Comic Strip Learning Media in Indonesian National Movement Materials - Dhoni Frizky Aryasaha; Andy Suryadi (University of Muhammadiyah Malang, 2024)
The study aims to (1) analyze the conditions of history learning at SMA N 12 Semarang, (2) describe the development of historical comic strip learning media, and (3) analyze the feasibility of historical comic strip learning media. The research uses the Research and Development with a modification of the 4D development model. Several stages are passed in this research, including definition, design, and development. The results of this research are (1) students need learning media, (2) development of historical comic strip learning media in Indonesian National Movement materials entitled “Story of Athar” with manual sketches, digitalization, and digital coloring until finalization, (3) feasibility validation product, namely 94% from material experts, 96% from media experts. The effectiveness of learning media in increasing students’ interest in learning is obtained from the results of the gain score using the formula for the difference between pre-test and post-test scores of 32,26%. Based on the results of this research, the scores of increasing students’ interest in learning in class XI F 11 are included in the High category because the gain score is 0,767 and is in the range g > 0,7.